2006
DOI: 10.1007/s10552-005-0412-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Regarding Overweight, Exercise, and Health among Blacks (United States)

Abstract: Some Blacks may underestimate the extent of their overweight, perhaps resulting from the high prevalence of the condition in the population. Gaps exist in Blacks' recognition of the connection between weight and health, although the importance of exercise for health promotion was widely acknowledged. These data may highlight an important target for intervention attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Table 5 Pays attention to body weight v. body size preference and body weight perception: male and female migrants of non-Western origin residing in Amsterdam, 2003Amsterdam, -2004 prevalence in the general population may influence body size preference as speculated by Cash et al in their study of changes of body image among US college students (48) and by Bennett et al in a study of attitudes towards overweight in African Americans (49) . Finally, although the figural stimuli used in our study have not been validated for the Turkish and Moroccan populations, similar instruments have been widely used in various study populations which lends support to our choice of instrument (19,20,25,50) .…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 Pays attention to body weight v. body size preference and body weight perception: male and female migrants of non-Western origin residing in Amsterdam, 2003Amsterdam, -2004 prevalence in the general population may influence body size preference as speculated by Cash et al in their study of changes of body image among US college students (48) and by Bennett et al in a study of attitudes towards overweight in African Americans (49) . Finally, although the figural stimuli used in our study have not been validated for the Turkish and Moroccan populations, similar instruments have been widely used in various study populations which lends support to our choice of instrument (19,20,25,50) .…”
Section: Discussionmentioning
confidence: 99%
“…Generic messages of a patient's overweight (i.e. those that do not discuss the clinical thresholds of overweight in some detail, provide a description of the health risks associated with overweight and obesity), or non-comprehensive counseling may have little effect, particularly given that many Blacks do not recognize the health consequences of overweight and obesity [11] and may not be readily motivated by weight-related aesthetic concerns. However, as weight status misperception may also protect against eating and body image disorders (which are less common among Blacks), misperception correction strategies should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Blacks appear to have a greater social acceptance of overweight, less body weight dissatisfaction, and higher body weight ideals compared to Whites [2-8]. Additionally, emerging evidence in nationally-representative cohorts suggest that Blacks, and to a lesser extent Hispanics, may have lower rates of perceived overweight compared to Whites [9-11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Bennett and colleagues 13 have suggested that the low rates of perceived overweight among African Americans may be in part due to the tendency to base one's perception of weight on social comparisons rather than clinical guidelines. Lay people, particularly people of lower socioeconomic status and African Americans, have different perceptions of what a "satisfactory" body size looks like, and factors not relevant to medical definitions clearly influence such perceptions.…”
Section: Body Size Perceptions Among African Americans -Baruth Et Almentioning
confidence: 99%